2008
DOI: 10.1038/ng.138
|View full text |Cite
|
Sign up to set email alerts
|

Altered brain microRNA biogenesis contributes to phenotypic deficits in a 22q11-deletion mouse model

Abstract: Individuals with 22q11.2 microdeletions show behavioral and cognitive deficits and are at high risk of developing schizophrenia. We analyzed an engineered mouse strain carrying a chromosomal deficiency spanning a segment syntenic to the human 22q11.2 locus. We uncovered a previously unknown alteration in the biogenesis of microRNAs (miRNAs) and identified a subset of brain miRNAs affected by the microdeletion. We provide evidence that the abnormal miRNA biogenesis emerges because of haploinsufficiency of the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
653
1
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 556 publications
(714 citation statements)
references
References 49 publications
41
653
1
5
Order By: Relevance
“…3,4 Interestingly, principal effectors of RNAi -miRNA and siRNA -have been shown to have an essential role in the development and function of the central nervous system (CNS). 6,8,15 In addition, several authors have demonstrated relevant developmental brain defects in animal models deficient for AGO proteins 5,7 including a reduction in total number of neurons and glia. 5 On the basis of these findings, we speculate that haploinsufficiency of AGO genes at this locus has contributed to the neurocognitive deficits observed in our patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Interestingly, principal effectors of RNAi -miRNA and siRNA -have been shown to have an essential role in the development and function of the central nervous system (CNS). 6,8,15 In addition, several authors have demonstrated relevant developmental brain defects in animal models deficient for AGO proteins 5,7 including a reduction in total number of neurons and glia. 5 On the basis of these findings, we speculate that haploinsufficiency of AGO genes at this locus has contributed to the neurocognitive deficits observed in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] In humans, the neuropsychiatric features seen in patients with 22q11.2 microdeletion syndrome are thought to result from haploinsufficiency of the DGCR8 gene and associated perturbations in miRNA biogenesis. 9 We present five patients with different but overlapping deletions involving the 1p34.3 locus, ranging in size from 1.1 to 3.1 Mb.…”
Section: Introductionmentioning
confidence: 99%
“…22q11DS mouse models present with a loss of glutamatergic synapses, decreased spine density, decreased CA1 pyramidal neuron complexity and reduced neurogenesis in the subventricular zone. The same mice show behavioural abnormalities in PPI, hyperlocomotion, fear conditioning and working memory [89][90][91][92][93][94] . 22q11DS is the only confirmed recurrent structural mutation associated with schizophrenia identified to date 95 .…”
Section: Q11mentioning
confidence: 99%
“…22 Haploinsufficiency of DGCR8 in mice causes abnormal miRNA processing and induces behavioral and neuronal deficits similar to a subset of symptoms observed in DiGeorge syndrome. 23 The C-terminal portion of the 773-residue DGCR8 protein (residues 499-751) contains two double-stranded RNA-binding domains (dsRBDs) and a conserved C-terminal tail (CTT) that are sufficient for pri-miRNA processing. 18,24 The N-terminal portion of DGCR8 (residues 1-275) is required for nuclear localization.…”
mentioning
confidence: 99%